2011
DOI: 10.5530/ax.2011.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Contents, Antioxidant Activities Cytotoxicity of Three Centaurea Species: C. calcitrapa subsp. calcitrapa, C. ptosimopappa C. spicata

Abstract: Background: Many species of the genus Centaurea have been reported to be used in Anatolian folk medicine. In the present study, methanolic and aqueous extracts of three species of Centaurea L. (C. calcitrapa subsp. calcitrapa, C. ptosimopappa and C. spicata) have been assessed for antioxidant and cytotoxic activities. Materials and Methods: Antioxidant activity was investigated by DPPH and superoxide anion scavenging and anti-lipid peroxidation assays. Cytotoxic effect on HeLa and Vero cells were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
(32 reference statements)
1
23
1
1
Order By: Relevance
“…In traditional medicine, C. species are used for fever, menstrual disorders, vaginal candidiasis, the treatment of liver, kidney and ulcer diseases, as antidiarrheal, stomachic, tonic, appetitive, antidiabetic, antipyretic, also as a diuretic and expectorant (6,7). Antiproliferative activity studies conducted on some Centaurea species in recent years have found that various extracts of these species significantly have antitumor activity (8)(9)(10)(11)(12)(13). In this study, the different extracts and fractions of active extract from aerial parts of C.kilaea were tested for antiproliferative activity against three human cancer cell lines (Hela; cervix adenocarcinoma, MCF-7; breast adenocarcinoma, PC-3; prostate adenocarcinoma) using MTT assay.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, C. species are used for fever, menstrual disorders, vaginal candidiasis, the treatment of liver, kidney and ulcer diseases, as antidiarrheal, stomachic, tonic, appetitive, antidiabetic, antipyretic, also as a diuretic and expectorant (6,7). Antiproliferative activity studies conducted on some Centaurea species in recent years have found that various extracts of these species significantly have antitumor activity (8)(9)(10)(11)(12)(13). In this study, the different extracts and fractions of active extract from aerial parts of C.kilaea were tested for antiproliferative activity against three human cancer cell lines (Hela; cervix adenocarcinoma, MCF-7; breast adenocarcinoma, PC-3; prostate adenocarcinoma) using MTT assay.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic effect of Centaurea extracts was tested in the human fibroblast cell (HS-68) using MTT assay. This test was based on the reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide to a colored formazan product by mitochondrial dehydrogenase [28]. The rested doses of Centaurea ethanolic extracts were determined based on previous studies [26,29,30].…”
Section: Protective Effect Against Induced Oxidative Stress In Humamentioning
confidence: 99%
“…In the Anatolian peninsula, the genus is represented by 190 species of more than 100 endemic species [5,6]. In Anatolia, different species are known as various common local names such as peygamber çiceği, zerdali dikeni, çoban kaldıran, timur dikeni, gökbaş, sarıbaş, acımık kötürüm, kotonkıran and boğa dikeni [7][8][9][10][11]. Many Centaurea species have traditionally been used for their antidiabetic, antidiarrheal, antirheumatic, anti-inflammatory, choleretic, digestive, gastric, diuretic, menstrual, astringent, hypotensive, antipyretic, cytotoxic and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%